2020
DOI: 10.1186/s13012-020-01025-8
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the 3HP Options Trial: a hybrid type 3 implementation-effectiveness randomized trial of delivery strategies for short-course tuberculosis preventive therapy among people living with HIV in Uganda

Abstract: Background: Recently, a 3-month (12-dose) regimen of weekly isoniazid and rifapentine (3HP) was recommended by the World Health Organization for the prevention of tuberculosis (TB) among people living with HIV (PLHIV) on common antiretroviral therapy regimens. The best approach to delivering 3HP to PLHIV remains uncertain. Methods: We developed a three-armed randomized trial assessing optimized strategies for delivering 3HP to PLHIV. The trial will be conducted at the Mulago Immune Suppression Syndrome (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Details of the trial design-including full eligibility criteria-have been published previously [14]. Briefly, the trial included adults (age �18 years) living with HIV engaged in care at the Mulago ISS clinic.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the trial design-including full eligibility criteria-have been published previously [14]. Briefly, the trial included adults (age �18 years) living with HIV engaged in care at the Mulago ISS clinic.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The trial protocol paper provides full details of the components of the 3 delivery strategies: facilitated DOT, facilitated SAT, and patient choice between facilitated DOT and facilitated SAT (with the assistance of a decision aid) [14]. Briefly, all strategies included (a) standardized patient counseling about the risks and benefits of 3HP; (b) streamlined clinic visits (11 visits for DOT and 2 for SAT) at the pharmacy window for symptom-based TB screening and side effects screening using a standardized checklist (S1 Text); (c) reimbursement of transport costs for clinic visits; and (d) automated interactive voice response (IVR) reminders for clinic visits.…”
Section: Randomization and Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are now conducting a randomized trial of different patient-centered treatment support approaches (directly observed therapy, self-administered therapy, or informed choice) to add empirical, quantitative findings to this body of evidence [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this qualitative study was to identify potential barriers to, and facilitators of, 3HP acceptance and completion, from the perspective of PLHIV in HIV/AIDS care and health workers at a large, urban HIV/AIDS clinic in Kampala, Uganda, and map these onto the COM-B model and BCW framework to identify suitable intervention functions. The goal was to inform the design of SAT and DOT delivery strategies for a type 3 hybrid effectiveness-implementation trial of 3HP [ 22 ].…”
Section: Introductionmentioning
confidence: 99%